A two-way switch for inositol pyrophosphate signaling: Evolutionary history and biological significance of a unique, bifunctional kinase/phosphatase. (January 2020) - Randall, Thomas A.; Gu, Chunfang; Li, Xingyao; Wang, Huanchen; Shears, Stephen B.
Abstract: The inositol pyrophosphates (PP-InsPs) are a unique subgroup of intracellular signals with diverse functions, many of which can be viewed as reflecting an overarching role in metabolic homeostasis. Thus, considerable attention is paid to the enzymes that synthesize and metabolize the PP-InsPs. One of these enzyme families - the diphosphoinositol pentakisphosphate kinases (PPIP5Ks) - provides an extremely rare example of separate kinase and phosphatase activities being present within the same protein . Herein, we review the current state of structure/function insight into the PPIP5Ks, the separate specialized activities of the two metazoan PPIP5K genes, and we describe a phylogenetic analysis that places PPIP5K evolutionary origin within the Excavata, the very earliest of eukaryotes. These different aspects of PPIP5K biology are placed in the context of a single, overriding question. Why are they bifunctional: i.e., what is the particular significance of the ability to turn PP-InsP signaling on or off from two separate 'switches' in a single protein?